Development of a micromolding process - Hung, N. P.; Yuan, S.; Lee, E. C. W.; Ali, Mohammad Yeakub (2001)
This paper presents the simulating and experimental results of a micromolding process for fabrication of threedimensional (3D) microcomponents. The maskless process utilizes a micro electrical discharging system for bulk machining, then finish machining using focused-ion beam to sputter the mold microcavity, which is then filled with various types of plastics. Simulation using commercially available software reveals possible problems in micromolding, and the simulation results of microgears (φ100-1000μm diameter, 1:1 aspect ratio) are compared with those from actually molded microgears. Although the software prohibits modeling of a stand-alone microgear with diameter below φ1000μm when using a 2.5D model and φ220μm for a 3D model, the simulation succeeds upon integrating a microgear of φ100μm with a larger base. Selecting the polymers from the built-in data bank, the simulation pinpoints locations for trapped gas, predicts filling time, volumetric shrinkage, uniformity, and distribution of pressure, shear rate, stress.... It correctly predicts underfilling of the cavity when the mold temperature is below a threshold, but fails to locate the weld lines. Minimum channel sizes for proper flow of several plastics are presented, and the mold temperature must be controlled for proper flow of polymer into a microcavity. The measured viscosity of tested polymers compliments the experimental and simulating results.